AN ANALYSIS OF STUDENTS’ ABILITY IN GRAMMAR MASTERY OF THREE ENGLISH TENSES AT THE TENTH GRADE STUDENTS’ OF SMKN 5 PADANG - Lailatul Husna; Yessy Marzona; Muharti Rosa Putri (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ekasakti, 2023)
The purpose of this research as to find out students' mistakes and difficulties in English tenses. This research was carried out at SMKN 5 Padang in the 2021/2022 academic year. The researcher conducted this research based on the findings in class. Many students were not able to make correct tenses well in learning and teaching activities.This researcher used descriptive method. The population in this research was 35 students at the tenth grade of SMKN 5 Padang, namely X TKJ (teknik komputer jaringan). In taking the sample the researcher used total sampling, so all population were samples, with the number of sample 35 students. The instrument of this research was a grammar test. In tecnique of collecting data the researcher asked students to use three tenses. In the data analysis, researcher used an assessment rubricThe results showed that the students' ability in grammar mastery, showed the total score of the students’ in using English tenses either in percentage score and mean score. The score showed that the students‟ ability in using English tenses was good. it is found that were sixteen students got good percentage (61.53%), and there were no one students got very poor percentage. The data also showed the total score of each tenses with mean score (62.88%). The researcher concluded that students grammatical errors in constructing three tenses English was good.